The role of fundamental movement skills on children's physical activity during different segments of the school day - Dongao Liu; Zan Huang; Yanjie Liu; Yulan Zhou (BMC, 2024)
Abstract Background Although prior studies have demonstrated that children with high levels of fundamental movement skill (FMS) are more active throughout the day, little is known about children's FMS and their physical activity (PA) during different segments of the school day (e.g., recess, lunch break, and physical education). The present study focused on FMS and moderate-to-vigorous PA (MVPA) during school day and identifies the association between children's FMS and MVPA during different segments of the school day in China. Methods A total of 322 children (boys n = 163, girls n = 159; Mage = 8.12, SD = 1.22 years) from four elementary schools involved in this study. Children's FMS and MVPA were measured using the Test of Gross Motor Development-2nd edition (TGMD-2) and hip-mounted accelerometers. Data such as height, weight, and socio-economic status (SES) were also obtained. Multilevel mixed regression models were used to examine the cross-sectional associations between FMS and MVPA. Models were adjusted for gender, age, standardized body mass index, and SES. Results Children engaged in 32.19 min of MVPA during the whole school day. Boys were more active than girls and had higher object-control skills competency. Locomotor skills were positively associated with children's long recess (B = 1.063) and short recess time (B = 1.502) MVPA. Object-control skills were positively correlated with children's MVPA time during long recess (B = 1.244) and physical education (PE) lessons (B = 1.171). Conclusion The findings highlight the importance of developing both locomotor and object-control skills in elementary schools to lead more MVPA engagement during different segments of the school day.